NIGHT VENTILATION STRATEGY ON HOUSING ESTATE IN WARM HUMID TROPIC WITH SURABAYA REFERENCE - Ima Defiana (Journal of Architecture&ENVIRONMENT, 2016)
This study is about night ventilation in dry climates often related to thermal mass. All the opening closed during daytime, to provide lower indoor temperature. According to bioclimatic context, Surabaya as warm humid reference, air movement is needed to restore humidity for all the time. This research concerned in promoting air movement, in order to maintain thermal comfort during night time. Opening schedule is proposed as factor which contributes the function of night ventilation in warm humid climate. Simulations were performed in steady state conditions, used models based on expanded-type 60 houses of grid pattern housing estates in Surabaya. 2 model site plan used as case studies. Air movement in bed room and living room has been investigated to maintain thermal comfort. Results show that night time ventilation in warm humid climate is accomplished by outdoor and indoor space configurations. The windows and door are proposed to open at 5.00 p.m. to 6.00 a.m. For supporting night time ventilation in warm humid, the outdoor space configurations are determined by building coverage ratio of 50-60%, 0.7 H/W at backside of building for wind paralell to the street or 1.3 H/W for wind perpendicular to the street. Occupants could expand thermal comfort zone with air flow of 0.4-0.8 m/sec for wind parralel to the street and 0.4-0.55 for wind perpendicular to the street.